Available evidence on HIFU for focal treatment of prostate cancer: a systematic review - Arnas Bakavicius; Giancarlo Marra; Petr Macek; Cary Robertson; Andre L. Abreu; Arvin K. George; Bernard Malavaud; Patrick Coloby; Pascal Rischmann; Marco Moschini; Ardeshir R. Rastinehad; Abhinav Sidana; et al. (International Brazilian Journal of Urology, 2022)
ABSTRACT Purpose: Prostate cancer (PCa) is the second most common oncologic disease among men. Radical treatment with curative intent provides good oncological results for PCa survivors, although definitive therapy is associated with significant number of serious side-effects. In modern-era of medicine tissue-sparing techniques, such as focal HIFU, have been proposed for PCa patients in order to provide cancer control equivalent to the standard-of-care procedures while reducing morbidities and complications. The aim of this systematic review was to summarise the available evidence about focal HIFU therapy as a primary treatment for localized PCa. Material and methods: We conducted a comprehensive literature review of focal HIFU therapy in the MEDLINE database (PROSPERO: CRD42021235581). Articles published in the English language between 2010 and 2020 with more than 50 patients were included. Results: Clinically significant in-field recurrence and out-of-field progression were detected to 22% and 29% PCa patients, respectively. Higher ISUP grade group, more positive cores at biopsy and bilateral disease were identified as the main risk factors for disease recurrence. The most common strategy for recurrence management was definitive therapy. Six months after focal HIFU therapy 98% of patients were totally continent and 80% of patients retained sufficient erections for sexual intercourse. The majority of complications presented in the early postoperative period and were classified as low-grade. Conclusions: This review highlights that focal HIFU therapy appears to be a safe procedure, while short-term cancer control rate is encouraging. Though, second-line treatment or active surveillance seems to be necessary in a significant number of patients.